1998
DOI: 10.1002/jlb.64.6.740
|View full text |Cite
|
Sign up to set email alerts
|

Thermal injury alters macrophage responses to prostaglandin E2: contribution to the enhancement of inducible nitric oxide synthase activity

Abstract: Prostaglandin E 2 (PGE 2 ) and macrophage (M) -derived reactive nitrogen intermediates (RNI) have been implicated in T cell dysfunction after thermal injury. Normally, M inducible nitric oxide synthase (iNOS) activity can be regulated by PGE 2 , however, it is unknown whether PGE 2 modulates M iNOS activity after thermal injury. Splenic M isolated from mice 7 days after thermal injury produced higher levels of RNI than M from sham mice when stimulated with lipopolysaccharide (LPS) or interferon-␥ (IFN-␥) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Suppression of PGE 2 production by inhibition of cyclooxygenase activity has been shown to improve immune function and survival post-burn [47]. Furthermore, PGE 2 can inhibit many aspects of macrophage function [48,49], and thermal injury also alters macrophage responses to PGE 2 [22,25]. Consistent with previous findings [24,50,51], macrophages from injured mice produced elevated amounts of PGE 2 .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Suppression of PGE 2 production by inhibition of cyclooxygenase activity has been shown to improve immune function and survival post-burn [47]. Furthermore, PGE 2 can inhibit many aspects of macrophage function [48,49], and thermal injury also alters macrophage responses to PGE 2 [22,25]. Consistent with previous findings [24,50,51], macrophages from injured mice produced elevated amounts of PGE 2 .…”
Section: Discussionsupporting
confidence: 60%
“…Mice received a third-degree full-thickness scald burn as previously described [7,10,25]. Briefly, the mice were anesthetized by intraperitoneal injection of 65 mg/kg body weight pentobarbital sodium, and the entire dorsal surface was shaved.…”
Section: Thermal Injury Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed using several animal injury models also demonstrated enhanced LPS reactivity by spleen-derived adherent cell populations and Kuppfer cells (5,15,16). Further investigations into the mechanisms associated with injury-induced perturbations in LPS responses indicated that changes in PGE 2 responses, IL-10 reactivity, and pertussis toxin-sensitive signaling pathways were involved (5,17,18). As a whole, these observations support the hypothesis that injury augments host inflammatory responses and that enhanced inflammatory reactivity may play a significant role in the development of SIRS and MODS following severe injury.…”
mentioning
confidence: 99%
“…Marano MA, 1990 andGamelli RL, 1995 documented increased systemic levels of these inflammatory mediators following burn injury altering the functional capacity of their parent cells. This elevated production of inflammatory mediators has thus been implicated for post-burn sepsis (Schwacha MG, 1998, Yang L, 1992, O'Riordain, MG, 1992. Locally released inflammatory mediators, i.e, C3a, C5a, PG, LT, O 2 -, NO, TNF , IL1, IL6, IL8, IL10, TGF act on different circulating cells (leukocytes/platelets) and other tissues (endothelium, epithelium and parenchymal cells) and neuro-endocrine axis to enhance different effector responses.…”
Section: Locally Released Inflammatory Mediators (Figure 6-7)mentioning
confidence: 99%